On the validity of using sympathomimetic drops in the treatment of habitually excessive tension of accommodation - T. N. Vorontsova; V. V. Brzhesky (Российский офтальмологический журнал, 2018)
Habitually excessive tension of accommodation is normally treated by two groups of drugs, cholinolytics and sympathomimetics. While the effect of cholinolytic drops can be fully explained by cholinergic innervation of the ciliary body, the issue of the adrenomimeticmedication target in the ciliary muscle remains debatable. The authors analyze literary data and the results of their own clinical studies to prove the existence of anatomical, physiological, pharmacological and clinical data on sympathetic innervation of the ciliary muscle alongside parasympathetic innervation thereof. Hence, the use of sympathomimetic drops in the treatment of children with habitually excessive tension of accommodation is validated both fundamentally and clinically. Yet, additional research in this area is required in order for an optimal strategy of drug therapy to be developed // Russian Ophthalmological Journal, 2016; 4: 80-9. doi: 10.21516/2072-0076-2016-9-4-80-89.